Treatment of Patients with Advanced Thyroid Cancer - Gomez-Saez, Jose M. (Current Biomarkers (Discontinued), 2016)
Background: Thyroid cancers are frequent in the endocrine system especially differentiated thyroid carcinoma and 95% of all thyroid cancer cases are differentiated neoplasmas. They have a favorable prognosis; however although, a small group present recurrence in 10-15% of patients following the standard treatment, surgery and radioiodine. Medullary thyroid carcinoma which is a neoplasm of the parafollicular C cells of the thyroid is responsible for a high number of thyroid cancer related deaths. Objective: Nowadays, the therapeutic options for advanced differentiated neoplasms, metastatic disease or anaplastic carcinoma are scarce. Recently, multitargeted kinase inhibitors are considered as new treatments for differentiated thyroid neoplasms and have been introduced in their management. The American Thyroid Association recommendations stated in the guideline of 2015 that tyrosine kinase inhibitors should be used in the treatment of patients with refractory differentiated thyroid carcinoma and in those cases that present progression. Methods: In this review, the purpose is to analyze the thyroid cancer tumorigeniesis and the action of the different targeted agents over these pathways of activation and the results in those cases of thyroid cancer without other possible treatments. Results: Multikinase inhibitors, the most widely studied, are able in thyroid cancer to interfere in the proliferation, invasion, and neoangiogenesis of neoplastic cells in thyroid cancer. Recently, the US Food and Drug Administration and the European Medicine Agency approved sorafenib and lenvatinib, which in Europe received an orphan designation by European Medicine Agency for follicular thyroid cancer. Some other controlled trials with tyrosine kinase inhibitors, as vandetanib and carbozantinib, have been finished and are now the two approved drugs in advanced medullary thyroid cancers. Conclusion: Thus, drug targeting represents a challenging approach with promising potential to circumvent some problems associated with many toxic effects of antineoplastic drugs.
Keywords: tyrosine kinase inhibitors